2012
DOI: 10.1007/s00438-012-0690-z
|View full text |Cite
|
Sign up to set email alerts
|

Allele diversity for the apoplastic invertase inhibitor gene from potato

Abstract: In planta the enzymatic activity of apoplastic and vacuolar invertases is controlled by inhibitory proteins. Although these invertase inhibitors (apoplastic and vacuolar forms) have been implicated as contributing to resistance to cold-induced sweetening (CIS) in tubers of potato (Solanum tuberosum L.), there is a lack of information on the structure and allelic diversity of the apoplastic invertase inhibitor genes. We have PCR-isolated and sequenced the alleles of the apoplastic invertase inhibitor gene (Stin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…In maize domestication was associated with strong selection of non-transcribed gene regions carrying a regulatory element in teosinte branched1 gene (Wang et al 1999). In HMG2 and SQE the greater sequence variation in introns was caused not only by the number of SNPs but also greater frequency of indels as it was found for an apoplastic invertase inhibitor gene in potato (Datir et al 2012). The lack of regulatory elements in the introns and major constrains on exon region due to pleiotropic effect of these primary metabolism genes could explain greater polymorphism on introns.…”
Section: Discussionmentioning
confidence: 69%
“…In maize domestication was associated with strong selection of non-transcribed gene regions carrying a regulatory element in teosinte branched1 gene (Wang et al 1999). In HMG2 and SQE the greater sequence variation in introns was caused not only by the number of SNPs but also greater frequency of indels as it was found for an apoplastic invertase inhibitor gene in potato (Datir et al 2012). The lack of regulatory elements in the introns and major constrains on exon region due to pleiotropic effect of these primary metabolism genes could explain greater polymorphism on introns.…”
Section: Discussionmentioning
confidence: 69%
“…The metabolic scheme shown in Figure 1 , however, suggests that this number does not include all important steps in starch biosynthesis and degradation. Furthermore, natural alleles of only few genes functional in starch-sugar interconversion have been characterized at the molecular level ( Datir et al 2012 ; Draffehn et al 2010 , 2012 ; Sowokinos et al 1997 ). DNA variants associated with tuber quality traits were initially discovered based on the analysis of SSCPs ( Dong and Zhu 2005 ), which were highly suitable for de novo discovery of DNA variation in specific loci but not for cost- and labor-effective high-throughput screenings in breeding programs ( Li et al 2005 , 2008 , 2013 ; Urbany et al 2011 ).…”
mentioning
confidence: 99%
“…5) 455 could be attributed to either the natural allelic variations of genes or changes in transcript levels. 456 Natural variation in candidate genes such as invertase and invertase inhibitors revealed that the 457 genetic polymorphism raises the possibility that SNPs in alleles of these genes may contribute to 458 the phenotypic variation in response to CIS among the potato genotypes (Menéndez et al, 2002;459 Baldwin et al, 2011;Datir et al, 2012;Datir et al, 2019). 460 461 Considerable variation in the levels of citrate and malate were observed in the present investigation 462 ( Fig.…”
Section: Putative Genes Controlling Cis Process Of Potato Tubers 436mentioning
confidence: 60%